PENGARUH FINANCIAL BOOTSTRAPPING, PERILAKU KEUANGAN DAN LITERASI KEUANGAN TERHADAP KINERJA KEUANGAN UMKM (STUDI KASUS UMKM NIGHT MARKET NGARSOPURO DI SURAKARTA) - Leta Novi Romadhoni; Naili Amalia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of financial bootstrapping, financial behavior, and financial literacy on the financial performance of MSMEs (case study of MSME Night Market Ngarsopuro in Surakarta). This research employs a quantitative approach using Slovin's formula, involving 135 respondents from MSMEs at the Night Market Ngarsopuro in Surakarta. Data were collected through questionnaires and analyzed using SPSS version 27. The data analysis methods used in this study include descriptive statistics, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and the coefficient of determination (R²) test.The results of the t-test indicate that financial bootstrapping, financial behavior, and financial literacy have a significant effect on financial performance. The F-test results show a calculated F value of 62.451 with a significance value (p-value) of = 0.000 < 0.05, thus Ho is rejected and Ha is accepted, meaning that the regression model is appropriate for predicting the influence of independent variables on the dependent variable. The coefficient of determination (R²) obtained is = 0.579, indicating that the contribution of the independent variables to the dependent variable is = 57.9%. The remaining (100% - 57.9%) = 42.1% is influenced by other variables outside the model, such as capital structure, financial technology and others.